Combining Nitrogen Isotopes and Redox Proxies Strengthens Paleoenvironmental Interpretations: Examples From Neoproterozoic Snowball Earth Sediments - Johnson, Benjamin W.; Mettam, Colin; Poulton, Simon W. (Frontiers in Earth Science, 2022)
The history of the nitrogen cycle on Earth is linked to the redox evolution of the surface environment. Many nitrogen cycle fluxes are microbially mediated, and the particular fluxes operating at any given time in an ecosystem depend on the presence, absence or abundance of oxygen. However, interpreting this relationship is complicated as several isotopic fractionations associated with N-cycling are not diagnostic of a particular redox state. Thus, linking nitrogen isotopic analyses with redox-sensitive proxies is essential when interpretating past environments. Specifically, we use concentrations of U, V and Mo, along with Fe-speciation, to augment and contextualize nitrogen isotopic measurements. As an example, we consider samples from the Neoproterozoic Cryogenian period to suggest that there was oxygenated water, with associated aerobic N cycle fluxes. This interpretation is based on positive $δ^{15}$N values between 4 to 8$\permil$, Fe-speciation data consistent with anoxic bottom water during the Snowball ocean and oxygenated after, and redox-sensitive trace metals indicative of oxic weathering and surface water. Typically, high $δ^{15}$N values are interpreted to reflect enhanced denitrification. We propose potential causes including a post-Snowball freshwater melt lid that suppressed deep water ventilation and that denitrification occurred more rapidly at high temperatures after the Snowball. These interpretations are buttressed by combined N isotope and redox analyses. This approach is especially useful during times of dynamic redox in the ocean-atmosphere system, to interpret biologic isotopic signals.